2015
DOI: 10.1088/1751-8113/48/5/055301
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum dynamics in the (non-Hermitian) Swanson oscillator

Abstract: Abstract. The non-Hermitian quadratic oscillator known as Swanson oscillator is one of the popular P T -symmetric model systems. Here a full classical description of its dynamics is derived using recently developed metriplectic flow equations, which combine the classical symplectic flow for Hermitian systems with a dissipative metric flow for the anti-Hermitian part. Closed form expressions for the metric and phasespace trajectories are presented which are found to be periodic in time. Since the Hamiltonian is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…It has been recently argued in [9] that a quasiclassical description of Bloch oscillations in the non-Hermitian case is of little use. Here, however, we show that the classical dynamics recently developed in [21][22][23][24] as a counterpart of non-Hermitian quantum dynamics, is capable of describing the main features of Bloch oscillations as well in the non-Hermitian case, as long as only a single Bloch band is involved in the dynamics (a constraint that also holds in the Hermitian case).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…It has been recently argued in [9] that a quasiclassical description of Bloch oscillations in the non-Hermitian case is of little use. Here, however, we show that the classical dynamics recently developed in [21][22][23][24] as a counterpart of non-Hermitian quantum dynamics, is capable of describing the main features of Bloch oscillations as well in the non-Hermitian case, as long as only a single Bloch band is involved in the dynamics (a constraint that also holds in the Hermitian case).…”
Section: Introductionmentioning
confidence: 81%
“…In the following we shall show, however, that while it may indeed be difficult to proceed directly from equation (25) for position and momentum, the semiclassical limit of the quantum dynamics generated by non-Hermitian Hamiltonians, as derived in [22] is capable of accurately describing basic features of the quantum dynamics. Using a Gaussian wavepacket approximation in the spirit of Heller [31], it has been shown that the classical dynamics associated to a non-Hermitian Hamiltonian = -H H H i R I , depending on the real valued canonical coordinates p q , are given by [22,23] (…”
Section: Quantum Dynamics and Quasiclassical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…where H + = x 4 /2 and H − = 2ixp + 1, which are Hermitian and anti-Hermitian respectively. It is interesting to note that, as H − = i{x, p}, by neglecting the anharmonic part of the potential H + , we are left with (a particular case of) the so-called Swanson Hamiltonian [27][28][29].…”
Section: A Hamiltonian Re-formulation Of the Problemmentioning
confidence: 99%
“…For example, the classical limit of the PT -symmetric quantum dynamics, described by generalized canonical equations, shows an interesting geometric structure [20,21] which provides a nontrivial extension of the Ehrenfest theorem. As shown in a series of papers by E.M. Graefe et al [20][21][22][23], the generalized canonical equations involve a metric gradient flow, in addition to the usual Hamiltonian (conservative) dynamics. The gradient flow is coupled to an evolution equation for the metric, which in turn depends on the phase space coordinates.…”
mentioning
confidence: 99%